Employees' experiences of education and knowledge in intellectual disability practice. Issue 3 (24th April 2020) - Olsson, Sylvia; Gustafsson, Christine
Abstract: Background: The value of support, service, and care in intellectual disability (ID) practice is linked to the competence of the professional caregivers. The quality of work is affected by the level of education of healthcare employees involved. Specific Aims: This study aimed to collect data on how employees perceive their education and training in ID practice and how educational programs prepare them for their working environment. Methods: We used a quantitative approach to investigate how employees reflect on their knowledge about ID and other disabilities and the sources of such knowledge. A total of 262 employees engaged in ID practice completed an online survey. Findings: The results indicated that education significantly influenced the participants' knowledge level, and highly specific education (i.e., workplace training) can substitute for work experience in ID practice. The authors conclude that all workplaces should examine their employees' skills regularly from the viewpoint of fulfilling the needs of people with ID. Discussion: Based on the results, it can be concluded that employees in ID practice need specific knowledge through workplace training (i.e., through hands‐on practice at the workplace). Competence development in the form of workplace training is needed to upskill the staff and possibly increases employees' participation at work.